2017
DOI: 10.1103/physrevlett.118.105003
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence Nonlinearities Shed Light on Geometric Asymmetry in Tokamak Confinement Transitions

Abstract: A comprehensive study of fully frequency-resolved nonlinear kinetic energy transfer has been performed for the first time in a diverted tokamak, providing new insight into the parametric dependences of edge turbulence transitions. Measurements using gas puff imaging in the turbulent L-mode state illuminate the source of the long known but as yet unexplained "favorable-unfavorable" geometric asymmetry of the power threshold for transition to the turbulence-suppressed H mode. Results from the recently discovered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 29 publications
(40 reference statements)
6
31
0
Order By: Relevance
“…Similar observations on GAMs have been reported in a recent investigation from JET [45], in which GAMs amplitudes measured by Doppler backscattering increase as the line-averaged density is raised. The competition between ZFs and GAMs has also been observed in earlier experiments in HL-2A [25] and Alcator C-Mod [29,46].…”
Section: B Different Behaviors Of Zonal Flows and Gamssupporting
confidence: 75%
“…Similar observations on GAMs have been reported in a recent investigation from JET [45], in which GAMs amplitudes measured by Doppler backscattering increase as the line-averaged density is raised. The competition between ZFs and GAMs has also been observed in earlier experiments in HL-2A [25] and Alcator C-Mod [29,46].…”
Section: B Different Behaviors Of Zonal Flows and Gamssupporting
confidence: 75%
“…12 Recent measurements using gas puff imaging inside the separatrix for LSN plasmas have shown that nonlinear transfer from turbulence to zonal flow is stronger in the favorable configuration than it is in the unfavorable one. 17 All these results show that the ion rB drift effect has its origin at the SOL and/or inside the separatrix. In contrast, it exhibits a similar or even lower P L-H with the ion rB drift away from the primary X-point in JET 18 and EAST 9 under all carbon walls or divertors, but the cause for this remains elusive.…”
Section: Introductionmentioning
confidence: 88%
“…The rB drift direction exhibits a significant influence on the access to H-modes. [9][10][11][12][13][14][15][16][17][18]21 However, the underlying physics mechanism is still unclear. Dedicated experiments were performed with matched plasma shapes and I P /B T pairs in upper single null (USN) plasmas in EAST with the ITER-like tungsten divertor.…”
Section: A Effects Of the $B Drift Directionmentioning
confidence: 99%
“…The density was reduced and the RF power increased over multiple shots in an attempt to decrease the pedestal collisionality prior to seeding. The underlying hypothesis was that geodesic acoustic modes (GAMs), which are observed in the I-mode ETB [23] [24], were being impacted by increased collisions, characterized by the total ion collision frequency, ν i = ν ii + ν iz , normalized to the GAM frequency, c S /R, where c S is the ion sound speed, 2T i /m i . If ν i R/c s becomes large, then the GAM could be broken up by collisions, and both ν i and c s depend on the impurity density.…”
Section: I/l Back-transition Phenomenologymentioning
confidence: 99%